2022
DOI: 10.7189/jogh.12.04071
|View full text |Cite
|
Sign up to set email alerts
|

The association of breastfeeding with cognitive development and educational achievement in sub-Saharan Africa: A systematic review

Abstract: Background Systematic reviews and meta-analyses of studies mainly from high-income countries suggest that breastfeeding improves cognitive function and educational achievement. However, these associations may be a manifestation of who breastfeeds in these settings rather than an actual effect of breastfeeding. We investigated the association of breastfeeding with cognitive development and educational achievements in sub-Saharan Africa, where breastfeeding is the norm, and socioeconomic status is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 53 publications
1
10
0
Order By: Relevance
“…Our results are consistent with existing literature on the association of breastfeeding with educational outcomes in sub-Saharan Africa [ 31 ]. For example, an analysis of data from the birth-to-twenty cohort study in South Africa found no effect of breastfeeding duration in infancy on subsequent educational outcomes among 17-year-olds [ 32 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our results are consistent with existing literature on the association of breastfeeding with educational outcomes in sub-Saharan Africa [ 31 ]. For example, an analysis of data from the birth-to-twenty cohort study in South Africa found no effect of breastfeeding duration in infancy on subsequent educational outcomes among 17-year-olds [ 32 ].…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, when Mitchell et al [ 33 ] studied 7–11-year-olds in rural KwaZulu-Natal, South Africa, they found no conclusive evidence of an association between exclusive breastfeeding and grade repetition. In addition, while our recent analysis of data from a Malawian cohort suggested an association between exclusive breastfeeding and age-for-grade attainment [ 34 ], in our earlier systematic review of data from sub-Saharan Africa, we found no effect of breastfeeding on cognitive development or educational achievement [ 31 ].…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…In fact, Renee et al who studied the extent to which confounding explained the association between breastfeeding duration and cognitive development up to 14 years of age, reported that adjusting for SES tended to halve the effect sizes, while further adjustment for maternal cognitive scores explained the remaining association at 5 years of age, while there was still an effect at ages 7, 11 and 14 (Pereyra‐Elías et al, 2022 ). In line with this, a systematic review of 17 studies in Sub‐Saharan Africa concluded that much of the effect of breastfeeding that is, exclusive or prolonged breastfeeding on child development has to do with ‘who breastfeeds’ and that confounders are rarely adequately considered in analyses (Mohammed et al, 2022 ). In fact, prolonged breastfeeding in itself has been associated with undernutrition in several studies (Briend & Bari, 1989 ; Syeda et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%